Pengaruh Partisipasi Anggaran Terhadap Budgetary Slack Dengan Psychological Capital Sebagai Variabel Pemoderasi - Tiwi Maitri Arista; Efrizal Syofyan (Universitas Negeri Padang, 2019)
The purpose of this research is to discover how the influence impact of budgetary participation on budgetary slack with psychological capital as a moderating variabel in structural leader and budget team, who are directly involved and have responsibilities for budgeting process in their fields and devises to solve the research problem. There for analysis used is a moderated regression analysis moderated regression analysis (MRA), the result shows that budgeting participation will improve and have a significant positive effect on budgetary slack in uncertainty and unexpected events while preparation and implementation of budgets at Bung Hatta University who was strengthened by psychological capital, which is a moderation in the relationship between budget, participation and budgetary slack.